DISPARITAS REGIONAL PROVINSI SUMATERA BARAT DI ERA OTONOMI DAERAH - S Syahrial; Dedi Budiman Hakim; Yeti Lis Purnamadewi (TATALOKA, 2015)
Regional autonomy policy has been implemented since 2001, but in 2013 as many as 66.67 percent of districts in West Sumatra still categorized as a relatively underdeveloped region by the Ministry of Development Underdeveloped regions. This indicates the occurrence of inequality considerable development in the Province of West Sumatra. This study not only examines the degree of inequality between regions, but also analyze the impact of GDRP per capita, the growth of the Human Development Index, and the Ratio of Infrastructure Expenditure against the inequalities based on economic position (the pattern and structure of economic growth). Analysis of the data use the Index Williamson and panel data regession from 2005 to 2012. The results showed disparity of regional development in the Provinces of West Sumatra increasing. Simultaneously and partially three independent variables (GDRP per capita, the growth of the Human Development Index, the Ratio of Infrastructure Expenditure) significant and positive influence as a major source of regional disparities in the Province of West Sumatra.Regional autonomy policy has been implemented since 2001, but in 2013 as many as 66.67 percent of districts in West Sumatra still categorized as a relatively underdeveloped region by the Ministry of Development Underdeveloped regions. This indicates the occurrence of inequality considerable development in the Province of West Sumatra. This study not only examines the degree of inequality between regions, but also analyze the impact of GDRP per capita, the growth of the Human Development Index, and the Ratio of Infrastructure Expenditure against the inequalities based on economic position (the pattern and structure of economic growth). Analysis of the data use the Index Williamson and panel data regession from 2005 to 2012. The results showed disparity of regional development in the Provinces of West Sumatra increasing. Simultaneously and partially three independent variables (GDRP per capita, the growth of the Human Development Index, the Ratio of Infrastructure Expenditure) significant and positive influence as a major source of regional disparities in the Province of West Sumatra.